Pembinaan Pasar Modal, Investasi Saham Dan Obligasi Pada Sekolah Menengah Kejuruan (SMK) Hang Nadim Batam - Efnita, Titik; Syaifullah, Syaifullah (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
Tri dharma higher education requires lecturers to carry out, research, warming and devotion to society. Therefore as a form of moral responsibility to the community to improve knowledge through formal education or non-formal. The purpose of this coaching is to introduce capital market products and how knowledge and costs for investments and costs. So far, people are still patterned with a project with a high cost and difficult for those who are afraid to invest, even if there is an investment community with a road to find a safe at home and maybe even raising. Investing in shares is something that is very important that the internet. These targets are students and teachers with the hope that these students will transmit their knowledge to the community. Existing benefits by using existing resources for other things offered for sale in terms of investment.Tri dharma higher education requires lecturers to carry out, research, warming and devotion to society. Therefore as a form of moral responsibility to the community to improve knowledge through formal education or non-formal. The purpose of this coaching is to introduce capital market products and how knowledge and costs for investments and costs. So far, people are still patterned with a project with a high cost and difficult for those who are afraid to invest, even if there is an investment community with a road to find a safe at home and maybe even raising. Investing in shares is something that is very important that the internet. These targets are students and teachers with the hope that these students will transmit their knowledge to the community. Existing benefits by using existing resources for other things offered for sale in terms of investment.